DEVELOPMENT PLANNING IN SONI VILLAGE DAMPAL SELATAN DISTRICT TOLI-TOLI DISTRICT - Maman Firmansyah, Andi; Izmi Humairah, Nurul; Al-Kafiah Samsu, M. Kafrawi (Berajah Journal, 2023)
This research aims to find out the process of preparing development planning in Soni Village, South Dampal District, ToilToli Regency. This research uses Bintoro Tjokroamidjojo's (2001) theory, namely preparing plans, establishing plans, implementing plans, and evaluating. The method used in this research is a qualitative descriptive method. Data collection was carried out by means of observation, interviews and documentation to collect the required data in the form of primary data and secondary data. Based on the results of this research, development planning in Soni Village, South Dampal District, Tolitoli Regency is still less effective, as for things that influence it, namely management from the government, and awareness from the community regarding the importance of participation in development planning in the village.